ENVIRONMENTAL LEARNING TO SHAPE STUDENTS’ PERCEPTION: THE INNOVATION STEPS IN WRITING POETRY - Dewi Syafrina (Jurusan Sastra Indonesia, 2018)
poetry This article aims to (1) to describe the contribution of environmental learning models in shaping students’ perception and (2) to conceptualize environmental learning as an effort to establish students’ perception in writing poetry. Environmental learning models guide teachers to involve the environment as teaching materials. Students’ interaction with the environment will be input that will shape students' perceptions of an object. The perception becomes an idea to make it easier for students to write poetry. Learning steps in this environmental learning model can be applied by Indonesian language teachers in guiding students to write poetry.